FAKTOR – FAKTOR YANG MEMPENGARUHI PENERAPAN KOMUNIKASI EFEKTIF OLEH PERAWAT DI RUANG RAWAT INAP - hilda hilda; noorhidayah noorhidayah; arsyawina arsyawina (MNJ (Mahakam Nursing Journal), 2017)
Cases of sentinel hospital often occur because of ineffective communication. Effective communication is the key for nurses to make patient safety based on the standard of patient safety in hospitals. This study aimed to analyze the factors that affect nurses in implementing effective communication in inpatient hospitals AW. Sjahranie Samarinda. The study was observational analytic with cross-sectional approach. The study was conducted in April and May 2016. The samples included 71 nurses drawn randomly. Instrument data collection using questionnaires and observation sheets. Data were analyzed with chi-square test and multivariate multiple logistic regression prediction models The results showed a significant difference between employment status, duration of work, ethics, language barriers and the preparation of communication with the implementation of effective communication. Long work and ethics is the most variable part of the implementation of effective communication with p <0.05. Conclusion: Long work and ethics are the factors that most influence the nurse in implementing effective communication in inpatient hospitals AW.Sjahranie. Keywords: Effective Communication - ethics, language barriers, openness, communication preparation, logistics.